Deriving Value from Social Commerce Networks - Stephen, Andrew T.; Toubia, Olivier (Journal of Marketing Research, 2010)
Social commerce is an emerging trend in which sellers are connected in online social networks and sellers are individuals instead of firms. This article examines the economic value implications of a social network between sellers in a large online social commerce marketplace. In this marketplace, each seller creates his or her own shop, and network ties between sellers are directed hyperlinks between their shops. Three questions are addressed: (1) Does allowing sellers to connect to each other create value (i.e., increase sales)? (2) What are the mechanisms through which this value is created? and (3) How is this value distributed across sellers in the network and how does the position of a seller in the network (e.g., its centrality) influence how much he or she benefits or suffers from the network? The authors find that (1) allowing sellers to connect generates considerable economic value, (2) the network's value lies primarily in making shops more accessible to customers browsing the marketplace (the network creates a “virtual shopping mall”), and (3) the sellers who benefit the most from the network are not necessarily those who are central to the network but rather those whose accessibility is most enhanced by the network.